Current Treatments for COVID-19: Application of Supercritical Fluids in the Manufacturing of Oral and Pulmonary Formulations - Helga K. Ruiz; Dolores R. Serrano; Lourdes Calvo; Albertina Cabañas (MDPI AG, 2022)
Even though more than two years have passed since the emergence of COVID-19, the research for novel or repositioned medicines from a natural source or chemically synthesized is still an unmet clinical need. In this review, the application of supercritical fluids to the development of novel or repurposed medicines for COVID-19 and their secondary bacterial complications will be discussed. We envision three main applications of the supercritical fluids in this field: (i) drug micronization, (ii) supercritical fluid extraction of bioactives and (iii) sterilization. The supercritical fluids micronization techniques can help to improve the aqueous solubility and oral bioavailability of drugs, and consequently, the need for lower doses to elicit the same pharmacological effects can result in the reduction in the dose administered and adverse effects. In addition, micronization between 1 and 5 µm can aid in the manufacturing of pulmonary formulations to target the drug directly to the lung. Supercritical fluids also have enormous potential in the extraction of natural bioactive compounds, which have shown remarkable efficacy against COVID-19. Finally, the successful application of supercritical fluids in the inactivation of viruses opens up an opportunity for their application in drug sterilization and in the healthcare field.